PENGEMBANGAN DESAIN PEMBELAJARAN PADA KELAS PROFESIONAL PGMI MENGGUNAKAN GOOGLE CLASSROOM - Niken Septantiningtyas (Edudeena : Journal of Islamic Religious Education, 2019)
Abstract: This research is a development research with the aim of designing the development of learning design in professional classes using Google classroom and group learning methods. The development of this design was tested by the feasibility test outlined by BSNP, namely regarding the eligibility of content, feasibility of presentation, and achievement of learning outcomes obtained an average percentage of 86.73% suitable to be applied in professional classes. In the professional class Google Classroom is very helpful in the lecture process so that all tasks can be completed in a timely manner and can be accessed from anywhere and anytime.   Abstrak: Penelitian ini adalah penelitian pengembangan yaitu dengan tujuan merancang pengembangan desain pembelajaran pada kelas profesional menggunakan google classroom dan metode pembelajaran berkelompok. Pengembangan desain ini diuji dengan uji kelayakan yang di jabarkan oleh BSNP yaitu mengenai kelakan isi, kelayakan penyajian, dan ketercapaian hasil pembelajaran didapatkan hasil prosentase rata-rata sebesar 86,73 percent layak untuk di terapkan dalam kelas profesional. Pada kelas profesional google clasroom sangat membantu dalam proses perkuliahan sehingga semua tugas dapat diselesaikan secara tepat waktu dan dapat diakses dari manapun dan kapanpun.